Fish as medicine: indigenous traditional knowledge and practices in Northeast India - Khesoh, Veselu; Phukan, Mayur Mausoom; Pankaj, Pranay Punj (Journal of Fisheries, 2026)
Northeast India, often referred to as the bio-geographical gateway of the country. It is home to rich biodiversity and diverse indigenous communities with deep-rooted traditional knowledge systems. Among these, ichthyofauna plays a pivotal role in ethnomedicinal practices, reflecting the intricate relationship between humans and their environment. This study aims to document and analyse the therapeutic applications of fish species traditionally used for healthcare in Northeast India. Through the PRISMA method, we identified and selected 21 articles reporting the use of fish as ethnomedicine in Northeast India. A total of 70 fish species from 27 families were identified, including Channa punctata and Monopterus cuchia, which are commonly used for respiratory and gastrointestinal ailments. Findings reveal that fish-based remedies are deeply integrated into the cultural and spiritual beliefs of local communities, emphasizing a holistic approach to health. This study highlights the potential of integrating traditional ichthyotherapeutic knowledge with modern medicine to create sustainable and culturally appropriate healthcare solutions. Furthermore, it underscores the importance of preserving this indigenous knowledge for future generations while ensuring ecological sustainability.